Integrasi Artificial Intelligence dalam Otomatisasi Perkantoran untuk Meningkatkan Efisiensi dan Produktivitas di Era Digital - Yunialdiarti Yuni; A.Sobandi; Abi Sopyan Febrianto (J-Coop : Journal of Co-operative, 2026)
In the digital Society 5.0 era, organizations are encouraged to leverage artificial intelligence (AI) technology to improve efficiency and productivity in office automation. This study aims to analyze the role and impact of AI on three main aspects of office automation: document management, communication, and decision-making processes. This research employs a library research method with a descriptive qualitative approach by reviewing various scientific sources such as journals, books, government reports, and credible publications. The findings indicate that AI implementation in document management reduces document retrieval time by up to 60% and increases data accuracy to 95%. In communication, AI-based technologies such as chatbots and digital collaboration platforms enhance employee satisfaction by 35% and accelerate response time by 45%. Meanwhile, AI-supported decision-making improves decision accuracy by up to 75% through real-time data analysis and predictive capabilities. The study concludes that AI integration significantly contributes to improving operational efficiency and productivity in office automation. However, challenges related to human resource readiness, data security, and infrastructure must be addressed to ensure optimal implementation.